Determinants of Islamic Banks’ Stability in Malaysia and Indonesia - Saddam, Siti Zaitun; Jaafar, Mohamad Nizam; Muhamat, Amirul Afif; Nizam, Nurien Syahirah Mohd; Halim, Nurin Aqilah (The Indonesian Capital Market Review, 2024)
The economic prosperity of any nation relies on its banking sector, which serves as the linchpin of the economy. This paper investigates key bank-specific factors influencing the stability of Islamic banks in Malaysia and Indonesia from 2012 to 2021. Using panel data analysis, the study identifies the fixed effect model as the optimal approach. The subsequent fixed effect regression analysis highlights the significance of the cost-to-income ratio in determining financial stability for both Malaysian and In- donesian Islamic banks. Notably the study reveals that the non-performing loan ratio is the primary stability indicator in Malaysia, while Indonesian counterparts prioritize maintaining a robust capital adequacy ratio. The study recommends vigilant regulatory oversight of capital adequacy and prudent expense management to safeguard banks against instability, fostering sustained financial health and success.